Constraints for small-scale private irrigation systems in the North Central zone of Nigeria: Insights from a typology analysis and a case study - Takeshima, Hiroyuki; Edeh, Hyacinth O. (International Food Policy Research Institute, 2017)
Agricultural transformation has been slow in Nigeria despite relatively fast growth in the non-agricultural sector of the economy. The limited contributions of irrigation in the agricultural sector have been considered to be one of the causes of slow agricultural transformation in Nigeria. Irrigation is used in both public-sector and private-sector irrigation schemes. Information is, however, often limited regarding small-scale private irrigation systems and their expansion potential and constraints, as compared to information on public irrigation schemes. This paper aims to provide various qualitative indicators which can shed light on irrigation system diversity and its recent evolution in Nigeria, as well as key economic characteristics of a selected private irrigation system as a case study.